2023
DOI: 10.1039/d3ra03268j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2/Al2O3 ratio on the electrochemical performance of amorphous zeolite loaded with cobalt oxide grown via steam-assisted crystallization method

Saureille Ngouana Moafor,
Patrice Kenfack Tsobnang,
Kabir Oyeniran Oyedotun
et al.

Abstract: The investigation of SiO2/Al2O3 ratio on electrochemical performance of amorphous zeolite loaded with cobalt oxide reveals that it is important to keep that ratio as high as possible for optimum supercapacitive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Specifically, the lowest ratio of Si and Al (corresponding to the ratio between silica and mullite) can be seen for the anthracite treated with a 10 mol/L alkaline solution, while the sodium ratio increases by elevating the alkaline concentration (Table 5). Therefore, it is suggested that the mixed alkali has a strong influence on the partition of SiO 2 and Al 2 O 3 in anthracite, causing a change in charge distribution between Si-O and Al-O bonds, thereby enhancing the polarization of chemical bonds and active centers (positive and negative charges) in the lattice, leading to bond relaxation in the tetrahedral structure of Si-O and Al-O bonds under the synergistic effect of time, temperature, and mixed alkali concentration, which would directly impact the zeolite transformation ratio [28]. The entire tetrahedral active core is exposed, the surface activation energy is increased, and the ion exchange capacity is enhanced so that Na+ enters the tetrahedral lattice to form a stable hole structure.…”
Section: Crystalline Structure Of Anthracite Modified Zeolite and Mag...mentioning
confidence: 99%
“…Specifically, the lowest ratio of Si and Al (corresponding to the ratio between silica and mullite) can be seen for the anthracite treated with a 10 mol/L alkaline solution, while the sodium ratio increases by elevating the alkaline concentration (Table 5). Therefore, it is suggested that the mixed alkali has a strong influence on the partition of SiO 2 and Al 2 O 3 in anthracite, causing a change in charge distribution between Si-O and Al-O bonds, thereby enhancing the polarization of chemical bonds and active centers (positive and negative charges) in the lattice, leading to bond relaxation in the tetrahedral structure of Si-O and Al-O bonds under the synergistic effect of time, temperature, and mixed alkali concentration, which would directly impact the zeolite transformation ratio [28]. The entire tetrahedral active core is exposed, the surface activation energy is increased, and the ion exchange capacity is enhanced so that Na+ enters the tetrahedral lattice to form a stable hole structure.…”
Section: Crystalline Structure Of Anthracite Modified Zeolite and Mag...mentioning
confidence: 99%